Development of A Conceptual Framework Based on The Lived Experiences of Indian Migrant Workers Using Social Determinants of Health Frame Work - P.R, Nikhil Raj; Khan, Imran; Kumar, Sreeraja (Journal of Neonatal Surgery, 2025)
The lived experience encompasses critical domain such as economic stability, education, neighbourhood and built environment, healthcare access, and social and community context of Indian migrant workers. To understand how Indian migrant workers, responds and adapt to such challenges, the present study aimed to develop a conceptual framework grounded through the lens of the Social Determinants of Health (SDOH) framework based on the lived experiences of Indian migrant workers. It provides a holistic understanding of how structural and environmental factors shape the health and well-being of migrant workers. Recognizing the uniqueness of these experiences, a qualitative phenomenological research design was adopted to elicit rich, in-depth narratives directly from the workers from Jana’s Contracting and Construction Company, located in La Plage-South-05, Pearl-Qatar. Data were collected using in-depth interviews guided by Open-ended questions rooted in Social Determinants of Health (SDOH) framework. Colaizzi’s method of phenomenological analysis was used to derive themes and subthemes, ensuring credibility and depth of interpretation. The findings revealed several interconnected themes: persistent job insecurity, exploitative employment practices, overcrowded accommodations, difficulty in accessing health care services, language and communication barriers, emotional distress including anxiety and depression, and the absence of institutional social support. However, many participants also demonstrated resilience through social bonding with co-workers, spiritual practices, and gradual cultural adaptation. Most notably, the study found that unmet health needs—particularly mental health—are a critical concern for this population, often overlooked due to their transient status and low visibility in health policy planning. A conceptual framework was developed to represent these processes holistically. This framework has potential applications in guiding migrants support systems, employment, housing, social integration, and health interventions, offering a theoretical foundation for future research and policy-making.